2018
DOI: 10.1038/s41431-018-0135-1
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotypic spectrum of variants in PDE4D/PRKAR1A: from acrodysostosis to acroscyphodysplasia

Abstract: Acrodysostosis (MIM 101800) is a dominantly inherited condition associating (1) skeletal features (short stature, facial dysostosis, and brachydactyly with cone-shaped epiphyses), (2) resistance to hormones and (3) possible intellectual disability. Acroscyphodysplasia (MIM 250215) is characterized by growth retardation, brachydactyly, and knee epiphyses embedded in cup-shaped metaphyses. We and others have identified PDE4D or PRKAR1A variants in acrodysostosis; PDE4D variants have been reported in three cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…Moreover, Caroline et al found a heterozygous variant at the same amino acid in PDE4D (p. Tyr677Asp) in a patient with acrodysostosis, suggesting that this tyrosine is critical for PDE4D protein function. However, this article focuses on phenotypic differences with different mutations, and further functional studies were not conducted (Michot et al, ). As a result of complex arrangement and alternative splicing of the PDE4D gene, multiple PDE4D protein variants with distinct N‐terminal sequences including or excluding domains critical for protein function have been identified in humans and in the mouse (Conti & Beavo, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Caroline et al found a heterozygous variant at the same amino acid in PDE4D (p. Tyr677Asp) in a patient with acrodysostosis, suggesting that this tyrosine is critical for PDE4D protein function. However, this article focuses on phenotypic differences with different mutations, and further functional studies were not conducted (Michot et al, ). As a result of complex arrangement and alternative splicing of the PDE4D gene, multiple PDE4D protein variants with distinct N‐terminal sequences including or excluding domains critical for protein function have been identified in humans and in the mouse (Conti & Beavo, ).…”
Section: Discussionmentioning
confidence: 99%
“…The N‐terminal upstream conserved regions 1 and 2 (UCR1 and UCR2) play crucial roles in forming an auto‐inhibitory domain to partially regulate the catalytic domain (Richter & Conti, ). More than 28 disease‐related PDE4D mutations have been reported to date, almost all of which are located in conserved domains, either in the UCR1, UCR2, or in the catalytic domain (Michot et al, ). It is reasonable to predict that the identified missense p.Y677S mutation positioned in the catalytic domain would affect the function of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exome testing did not identify mutations in the PDE4D or PRKAR1A genes known to cause acrodysostosis.These mutations can either reduce the amount of RIα protein, with a subsequent depletion of Protein Kinase A(Linglart et al, 2011), or alter the modulation of the levels of cAMP, generating resistance to several hormones(Lee et al, 2012). Individuals with PDE4D related acrodysostosis have a more pronounced midface hypoplasia and intellectual disability compared to PRKAR1A individuals(Michot et al, 2018).Lamellar ichthyosis and hand deformities are reported in psoriatic arthritis but onset is typically later in life. The proband's hand abnormalities and skin findings were present during early childhood and continue to progress during her life.…”
mentioning
confidence: 99%